PEMODELAN REGRESI SPASIAL DEPENDENSI PADA TINGKAT PARTISIASI ANGKATAN KERJA DI INDONESIA TAHUN 2020 - Usali, Rahmayunda; Nurwan, Nurwan; Oroh, Franky Alfrits; Payu, Muhammad Rezky Friesta (PATTIMURA UNIVERSITY, 2021)
This study discusses the regression modeling with spatial dependence to determine the factors affecting the labor force participation rate in Indonesia 2020. The spatial regression models used in this study are spatial Autoregressive Model (SAR) and Spatial Error Model (SEM), The finding concludes that the SAR model is better used in spatial modeling. At the same time, provincial minimum wage, the average length of school or educational level, and population are factors that affect the labor force participation rate in Indonesia 2020.